2012
DOI: 10.1088/1748-6041/7/3/035012
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of PEM-coated alginate microgels for controlled release of protein

Abstract: In this study, calcium-alginate microgels coated with a polyelectrolyte multilayer (PEM) were fabricated as a controlled-release system. This system was constructed via an electrostatic droplet generation technique followed by a layer-by-layer (LbL) self-assembly technique. The electrostatic droplet generation technique was reported as an easy method of preparing microgels, due to their mild preparation conditions and ability to preserve the biological activity of the encapsulated drugs. With the LbL self-asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 47 publications
(54 reference statements)
0
23
0
Order By: Relevance
“…bFGF‐loaded alginate Ms were prepared according to Zuo et al . (). Briefly, sodium alginate was dissolved in purified water to a concentration of 2.0% w/v, with overnight stirring at room temperature.…”
Section: Methodsmentioning
confidence: 97%
“…bFGF‐loaded alginate Ms were prepared according to Zuo et al . (). Briefly, sodium alginate was dissolved in purified water to a concentration of 2.0% w/v, with overnight stirring at room temperature.…”
Section: Methodsmentioning
confidence: 97%
“…Early studies have revealed that the layered coating structure could protect the drug more efficiently to realize the sustained release. [32] Meanwhile, most layered structures were microsized or had positive surface charge, which were unstable in the stomach, thus not suitable for the intestinal-specific drug delivery. In this study, the LBL-CN-DOX-IO nanoparticles showed a significant reduction of the initial rapid release of DOX from the amphiphilic inner polymer layer in the low pH conditions of the stomach fluid.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the gastric stability of the enzymes was increased by trapping them inside biopolymer microgels with an antacid [126]. BSA has been trapped inside alginate microgels by coating them with successive layers of cationic (chitosan) and anionic (dextran sulfate) biopolymers [127]. Insulin has been trapped inside hydroxypropyl cellulose-polyglutamic acid microgels, which enhanced its stability under gastric conditions [128].…”
Section: Biopolymer Microgelsmentioning
confidence: 99%